Identification of Urinary Biomarkers of Colon Inflammation in IL10-/- Mice Using Short-Column LCMS Metabolomics. (6th December 2010) - Otter, Don; Cao, Mingshu; Lin, Hui-Ming; Fraser, Karl; Edmunds, Shelley; Lane, Geoff; Rowan, Daryl
Abstract : The interleukin-10-deficient (IL10 -/- ) mouse develops colon inflammation in response to normal intestinal microflora and has been used as a model of Crohn's disease. Short-Column LCMS metabolite profiling of urine from IL10 -/- and wild-type (WT) mice was used, in two independent experiments, to identify mass spectral ions differing in intensity between these two genotypes. Three differential metabolites were identified as xanthurenic acid and as the glucuronides of xanthurenic acid and of α-CEHC (2, 5, 7, 8-tetramethyl-2-(2 ′ -carboxyethyl)-6-hydroxychroman). The significance of several differential metabolites as potential biomarkers of colon inflammation was evaluated in an experiment which compared metabolite concentrations in IL10 -/- and WT mice housed, either under conventional conditions and dosed with intestinal microflora, or maintained under specific pathogen-free (SPF) conditions. Concentrations of xanthurenic acid, α-CEHC glucuronide, and an unidentified metabolite m/z 495 - /497 + were associated with the degree of inflammation in IL10 -/- mice and may prove useful as biomarkers of colon inflammation.